Development of a Multidimensional Proteomic Approach to Detect Circulating Immune Complexes in Cattle Experimentally Infected With Mycobacterium bovis - Hadi, Syeda A.; Waters, Wade R.; Palmer, Mitchell; Lyashchenko, Konstantin P.; Sreevatsan, Srinand (Frontiers in Veterinary Science, 2018)
Objective: To evaluate a high-resolution method to identify pathogen-specific biomarkers in serum of calves infected with Mycobacterium bovis. Methods: Serum samples from four calves infected with M. bovis were collected before and after infection at weeks 9, 14, 15, 31, and 36. Immune-complex-associated mycobacterial antigens in the serum were enriched using an immunochromatography method termed, dual path platform (DPP). All regions of antigen capture zones, that consisted of monospecific rabbit polyclonal antibodies raised against M. tuberculosis lysates, on DPP strips were excised and analyzed by multidimensional proteomics. The resulting proteins were then passed through 4 rigorous peptide quality filters-false-hits, decoys, non-M. tuberculosis complex proteins were all removed followed by individual quality check of those remaining. Peptides were then checked on NCBI's BLASTp for M. tuberculosis complex specificity. Results: Proteins in 2 of the animals passed the multipronged-highly stringent peptide quality analysis. Animal#54 had 7 unique M. tuberculosis complex proteins at week 14 post-infection, while animal#56 had 4 at week 36 post-infection along with 1 immunoglobulin. Conclusion:M. tuberculosis complex -specific peptides identified in this study were identified in 2 animals and at 2 separate time points post infection. Further studies with better enrichment protocols and using larger sample sizes and replications are required to develop a TB-specific diagnostic tool for bovine tuberculosis.